2020
DOI: 10.21203/rs.3.rs-92708/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Helmet CPAP to Treat Hypoxic Pneumonia Outside the ICU: An Observational Study During the COVID-19 Outbreak

Abstract: Background: Respiratory failure due to COVID-19 pneumonia is associated with high mortality and may threaten healthcare systems hold, due to the surge patients requiring advanced respiratory support. Shortage of intensive care unit (ICU) beds required many patients to be treated outside the ICU despite severe hypoxia. Helmet is as effective interface to provide Continuous Positive Airway Pressure (CPAP) non-invasively. We report data about the usefulness of helmet CPAP during pandemic, either as an effective t… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
9
1

Year Published

2021
2021
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(11 citation statements)
references
References 20 publications
(52 reference statements)
1
9
1
Order By: Relevance
“…Very interestingly, the paper by Avdeev and coworkers shows a difference (albeit statistically non significant) between success and failure in the values of PaO 2 /FiO 2 only if these were during NIV as opposed to standard oxygen. This is totally in line with a recent finding by Coppadoro et al (9) and emphasizes that PaO 2 /FiO 2 has a prognostic value for NIV failure only if measured during NIV. At the same time, we fully agree with Avdeev, Yaroshetskiy and Nuralieva (10): considering the risk of Patient Self Inflicted Lung Injury is of paramount importance during NIV and their finding on the role of minute ventilation is extremely relevant.…”
Section: To the Editorsupporting
confidence: 92%
See 1 more Smart Citation
“…Very interestingly, the paper by Avdeev and coworkers shows a difference (albeit statistically non significant) between success and failure in the values of PaO 2 /FiO 2 only if these were during NIV as opposed to standard oxygen. This is totally in line with a recent finding by Coppadoro et al (9) and emphasizes that PaO 2 /FiO 2 has a prognostic value for NIV failure only if measured during NIV. At the same time, we fully agree with Avdeev, Yaroshetskiy and Nuralieva (10): considering the risk of Patient Self Inflicted Lung Injury is of paramount importance during NIV and their finding on the role of minute ventilation is extremely relevant.…”
Section: To the Editorsupporting
confidence: 92%
“…In regard to the lower mortality observed in the nice study by Nightighale et al (7), this was recorded in a much younger population than ours (52 vs 68 years old), while the study from Brusasco et al (8) did not include patients not eligible for resuscitation (as opposed to our study, where 28% of patients had a do not intubate decision). Moreover, the baseline PaO 2 /FiO 2 reported in both papers was collected prior to CPAP initiation: since CPAP rapidly and significantly improves PaO 2 /FiO 2 (9) as also shown in table 1 by Avdeev and coworkers, the severity of the populations are not comparable with ours.…”
Section: To the Editorcontrasting
confidence: 51%
“…During a pandemic, when the demand for critical care resources exceeds the available capacity, 12 use of non-invasive respiratory support in an individual patient in the absence of established evidence might be viewed as the only possible treatment, particularly if there is no option to participate in a clinical trial. However, where there are no critical care capacity issues and options to participate in a clinical trial exist, clinicians should be mindful that provision of this treatment outside the rigorous infrastructure of RCTs represents random empirical care.…”
mentioning
confidence: 99%
“…24 Specific NIV studies in COVID-19 largely focused on the use of CPAP in the non-ICU setting (Table 3). [183][184][185][186][187][188][189][190][191][192][193][194][195][196] Unfortunately 46% of these were research letters often lacking pertinent data. [183][184][185][186][187][188] Nonetheless, 71% of all studies reported relatively low failure rates of 11-28%; and relatively low associated mortality among those without care limitations (< 30%).…”
Section: Lung Recruitment Potentialmentioning
confidence: 99%